Recanalization by Mechanical Embolus Disruption during Intra-Arterial Thrombolysis in the Carotid Territory - Sorimachi, Takatoshi; Fujii, Yukihiko; Tsuchiya, Naoto; Nashimoto, Takeo; Harada, Atsuko; Ito, Yasushi; Tanaka, Ryuichi (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Mechanical disruption of a clot with a microcatheter and a guidewire has not been detailed in conjunction with intra-arterial thrombolysis in patients with acute ischemic stroke. The purpose of this study was to evaluate the efficacy of mechanical disruption of an embolus in the carotid artery distribution.METHODS: We analyzed clinical and radiologic findings and functional outcomes 3 months after thrombolysis with mechanical disruption. Outcomes were classified as good for modified Rankin scale (mRS) scores of 0–2, moderate for mRS scores of 3, and poor for death and mRS scores of 4 or 5.RESULTS: Twenty-three consecutive patients with severe hemispheric symptoms were treated with several methods of mechanical embolus disruption during the intra-arterial administration of urokinase. Twelve patients had occlusions of the proximal middle cerebral artery (MCA), and 11 had occlusions of the distal internal carotid artery (ICA). Recanalization was observed in all patients with MCA occlusions and in 10 (91%) with ICA occlusions. Outcomes were good in nine patients (75%) with MCA occlusions and in four (36.4%) with ICA occlusions. Early management of vessel perforation, caused by a microguidewire tip in two patients, resulted in early hemostasis. Neither patient had a major deficit attributable to the complication.CONCLUSION: A high incidence of recanalization and clinical improvement can be observed in patients with occlusions of not only the proximal MCA but also the distal ICA. This method might be an effective additional option to intra-arterial thrombolysis for acute distal ICA and proximal MCA occlusions.